MENINGKATKAN PRESTASI DAN HASIL BELAJAR SISWA PADA FASE A - Eric Dwi Virgantoro; Moh Ainor Rofiqi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze effective strategies for improving students' academic performance and learning outcomes in Phase A (early primary education) using the Systematic Literature Review (SLR) method. Phase A is a critical stage in student development, where foundational cognitive, social, and emotional skills are established. This research reviewed and analyzed 25 scholarly articles from various indexed journals, selected based on their relevance to the topic and publication quality. The review results indicate that active learning approaches, technology integration, and strengthening parental involvement significantly enhance students' learning outcomes. Moreover, the role of teachers as facilitators of interactive learning and providers of constructive feedback has proven effective in boosting students' motivation and engagement in the learning process. This article concludes that implementing holistic and student-centered strategies positively impacts students' academic performance and learning outcomes. The recommendations from this study include developing student-centered learning programs, providing intensive training for teachers on innovative methods, and enhancing collaboration between schools and parents. This research provides valuable contributions to the development of educational theory and practice in Phase A to support students' academic achievement optimally.